2020
DOI: 10.1016/j.matlet.2020.127597
|View full text |Cite
|
Sign up to set email alerts
|

Atypical electrical behavior of few layered WS2 nanosheets based platform subject to heavy metal ion treatment

Abstract: An atypical electrical behavior of WS2 nanosheets deposited on Cu electrodes is reported here. The characteristic Raman peaks at 355cm -1 and 421.8cm -1 confirm the few-layer structure of WS2. The addition of heavy metal ions of ~30µl on this platform results in non-ohmic behavior in I-V characteristics, accompanied by a dramatic rise of current from nA to µA. Additionally, this atypical behavior is found to be reversible. Subsequent to removal of these ions from the nanosheets, it again exhibits normal ohmic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…[ 34 ] Following the very established scheme, it has been observed that the current–voltage ( I–V ) characteristics of the untreated WS 2 nanosheets deposited on copper electrodes exhibit linear behavior without any fluctuations, as shown in Figure 1d. [ 34,35 ] However, as discussed, it is quite possible to generate and tune noise fluctuations in layered system by changing the ambient condition and preparation process. The ideal linear characteristics of the resistive system can be obtained by drop‐casting ≈100 μL of dispersed WS 2 nanosheets for three times on the top of finger‐like electrode system followed by 9 h of vacuum drying after each drop‐casting as shown in Figure 1d.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 34 ] Following the very established scheme, it has been observed that the current–voltage ( I–V ) characteristics of the untreated WS 2 nanosheets deposited on copper electrodes exhibit linear behavior without any fluctuations, as shown in Figure 1d. [ 34,35 ] However, as discussed, it is quite possible to generate and tune noise fluctuations in layered system by changing the ambient condition and preparation process. The ideal linear characteristics of the resistive system can be obtained by drop‐casting ≈100 μL of dispersed WS 2 nanosheets for three times on the top of finger‐like electrode system followed by 9 h of vacuum drying after each drop‐casting as shown in Figure 1d.…”
Section: Resultsmentioning
confidence: 99%
“…. [34,35] However, as discussed, it is quite possible to generate and tune noise fluctuations in layered system by changing the ambient condition and preparation process. The ideal linear characteristics of the resistive system can be obtained by drop-casting %100 μL of dispersed WS 2 nanosheets for three times on the top of finger-like electrode system followed by 9 h of vacuum drying after each drop-casting as shown in Figure 1d.…”
Section: Figure 1dmentioning
confidence: 99%
“…The monolayer of TMDs consists of positively charged layers of metal cations (M) sandwiched between two negatively charged layers of chalcogenide (X) anions. [93,94] Although the M-X intralayer bonds are very strong (ionic covalent), the MX 2 nanosheets are stacked and held together by weak vdW attractions. As a result, their parent layered crystal can be exfoliated into a single and or few layers using similar methods that are used for the exfoliation of graphene.…”
Section: Transition Metal Dichalcogenides (Tmds)mentioning
confidence: 99%
“…Besides MoS 2 , tungsten dichalcogenides are also receiving attention from researchers for their application in HMI detection. Neog et al first described the potential of WS 2 as a chemiresistor sensor for the detection of HMIs [ 235 ]. The result of his studies showed that the I-V characteristic of the untreated (bare) WS 2 -chemiresistor was linear in the voltage range of −9 V to 9 V and the maximum current obtained was in n A scale.…”
Section: Transition Metal Dichalcogenides (Tmds)-based Fetsmentioning
confidence: 99%